2005
DOI: 10.1016/j.femsim.2004.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Towards more virulent and antibiotic-resistantSalmonella?

Abstract: Salmonella are well-known pathogens. Virulence determinants can be present on the chromosome, usually encoded on pathogenicity islands, or on plasmids and bacteriophages. Antibiotic resistance determinants usually are encoded on plasmids, but can also be present on the multidrug resistance region of Salmonella Genomic Island 1 (SGI1). Virulence plasmids show a remarkable diversity in the combination of virulence factors they encode, which appears to adapt them to specific hosts and the ability to cause gastroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 44 publications
(56 reference statements)
5
124
1
6
Order By: Relevance
“…Using antimicrobial agents for cattle have been implicated as a source of human infection with antimicrobial resistant (AMR) Salmonella through direct contact with livestock and consumption of raw milk, meat and contaminated materials (Alexander et al, 2009). Antimicrobial resistant Salmonella are increasing due to the use of antimicrobial agents in food animals at subtherapeutic level or prophylactic doses for growth promotion and markedly increase the human health risks associated with consumption of contaminated milk and meat products (Endrias Zewdu and Cornelius 2009), through mutation, acquisition of resistance encoding genes (Fluit, 2005) and irrational use of antimicrobials in food animals (Fluit, 2005;Takele Beyene and Berihun Tesega, 2014). Different studies conducted in Ethiopia revealed fragmented substantial prevalence as well as antimicrobial susceptibility of Salmonella in veterinary and public health setups (Daniel Alemayehu et al, 2003;Bayleyegn Molla et al, 2003;Getahun Ejeta et al, 2004;Wassie Molla et al, 2006;Endrias Zewdu and Cornelius, (2009);Zelalem Addis et al, 2011;Deresse Hailu et al, 2015;Takele Beyene et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Using antimicrobial agents for cattle have been implicated as a source of human infection with antimicrobial resistant (AMR) Salmonella through direct contact with livestock and consumption of raw milk, meat and contaminated materials (Alexander et al, 2009). Antimicrobial resistant Salmonella are increasing due to the use of antimicrobial agents in food animals at subtherapeutic level or prophylactic doses for growth promotion and markedly increase the human health risks associated with consumption of contaminated milk and meat products (Endrias Zewdu and Cornelius 2009), through mutation, acquisition of resistance encoding genes (Fluit, 2005) and irrational use of antimicrobials in food animals (Fluit, 2005;Takele Beyene and Berihun Tesega, 2014). Different studies conducted in Ethiopia revealed fragmented substantial prevalence as well as antimicrobial susceptibility of Salmonella in veterinary and public health setups (Daniel Alemayehu et al, 2003;Bayleyegn Molla et al, 2003;Getahun Ejeta et al, 2004;Wassie Molla et al, 2006;Endrias Zewdu and Cornelius, (2009);Zelalem Addis et al, 2011;Deresse Hailu et al, 2015;Takele Beyene et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The exchange of resistance plasmids between members of Enterobacteriaceae will severely limit the treatment options of infections caused by these microorganisms, which are responsible for nearly half of all infections (Fluit, 2005). Many ESBLs-mediated plasmids also contain virulence genes or regulate their expression; this confers survival advantage in an unfavorable drug environment and constitutes a new tool in the bacterial evolution (Guerra et al, 2002;Martinez and Baquero, 2002;Chu and Chiu, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…They are the major cause of food-born bacterial diseases. They cause a wide range of clinical illness: enteric fever, gastroenteritis, and bacteraemia, particularly in infants and in immunocompromised patients (Fluit, 2005). The incidence of salmonellosis is rising in the most of countries, which become one of the public health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies had reported large hybrid virulence-resistance plasmids in serovars Typhimurium, Choleraesuis and Enteritidis, isolated from Spain, Italy, Czech Republic, Taiwan and the United Kingdom (Chu et al, 2001;Guerra et al, 2001;Guerra et al, 2002;Guerra et al, 2004;Villa and Carattoli 2005;Chu and Chiu 2006;Herrero et al, 2008a;Herrero et al, 2008b;Hradecka et al, 2008;Herrero et al, 2009;Rodriguez et al, 2011). In some of the studies it was demonstrated that the hybrid plasmids were conjugative, which may lead to their spread to new recipients and allow the co-selection of the antibiotic and virulence genes, representing a hazard to human and animal health (Fluit 2005).…”
Section: Antimicrobial Resistance and Virulence Plasmidsmentioning
confidence: 99%